The HSV1 Tail-Anchored Membrane Protein pUL34 Contains a Basic Motif That Supports Active Transport to the Inner Nuclear Membrane Prior to Formation of the Nuclear Egress Complex - Christina Funk; Débora Marques da Silveira e Santos; Melanie Ott; Verena Raschbichler; Susanne M. Bailer (Viruses, 2021)
Herpes simplex virus type 1 nucleocapsids are released from the host nucleus by a budding process through the nuclear envelope called nuclear egress. Two viral proteins, the integral membrane proteins pUL34 and pUL31, form the nuclear egress complex at the inner nuclear membrane, which is critical for this process. The nuclear import of both proteins ensues separately from each other: pUL31 is actively imported through the central pore channel, while pUL34 is transported along the peripheral pore membrane. With this study, we identified a functional bipartite NLS between residues 178 and 194 of pUL34. pUL34 lacking its NLS is mislocalized to the TGN but retargeted to the ER upon insertion of the authentic NLS or a mimic NLS, independent of the insertion site. If co-expressed with pUL31, either of the pUL34-NLS variants is efficiently, although not completely, targeted to the nuclear rim where co-localization with pUL31 and membrane budding seem to occur, comparable to the wild-type. The viral mutant HSV1(17+)Lox-UL34-NLS mt is modestly attenuated but viable and associated with localization of pUL34-NLS mt to both the nuclear periphery and cytoplasm. We propose that targeting of pUL34 to the INM is facilitated by, but not dependent on, the presence of an NLS, thereby supporting NEC formation and viral replication.